Effects of transcranial direct current stimulation on brain network connectivity and complexity in motor imagery. (13th July 2021) - Yang, Kangbo; Xi, Xugang; Wang, Ting; Wang, Junhong; Kong, Wanzeng; Zhao, Yun-Bo; Zhang, Qizhong
Highlights: A new experimental paradigm for exploring the different effects of anode tDCS on M1 and SMA. The tDCS's effect on the brain-SMA is more obvious in the motor preparation stage. The effect of tDCS is more obvious in the execution of the entire motor imagination task, but not in the motor preparation stage. The effect of tDCS on the motor area of the brain is significant, especially in the M1. Abstract: Related experiments have shown that transcranial direct current stimulation (tDCS) anodal stimulation of the brain's primary motor cortex (M1) and supplementary motor area (SMA) can improve the motor control and clinical manifestations of stroke patients with aphasia and dyskinesia. In this study, to explore the different effects of tDCS on the M1 and SMA in motor imagery, 35 healthy volunteers participated in a double-blind randomized controlled experiment. Five subjects underwent sham stimulation (control), 15 subjects underwent tDCS anode stimulation of the M1, and the remaining 15 subjects underwent tDCS anode stimulation of the SMA. The electroencephalogram data of the subjects' left- and right-hand motor imagery under different stimulation paradigms were recorded. We used a functional brain network and sample entropy to examine the different complexities and functional connectivities in subjects undergoing sham-tDCS and the two stimulation paradigms. The results show that tDCS anodal stimulation of the SMA produces less obvious differences in the motor preparation phase, while tDCS anodal stimulation of the M1 produces significant differences during the motor imaging task execution phase. The effect of tDCS on the motor area of the brain is significant, especially in the M1.